INNOVATIVE METHODS OF TEACHING TO ADULT LEARNERS - Umaraliyeva Munojotkhon Mashrabovna; Marufova Sarvinoz Murotjon kizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: The article is devoted to the description of innovative methods for teaching adults. Innovative teaching methods and technologies are gaining traction today, as are new opportunities associated with the establishment of interpersonal interaction. The author focuses on method selection, which should vary depending on the purpose, age group, and stage of mental development.